2004
DOI: 10.1073/pnas.0301885101
|View full text |Cite
|
Sign up to set email alerts
|

A fluorophore attached to nicotinic acetylcholine receptor βM2 detects productive binding of agonist to the αδ site

Abstract: To study conformational transitions at the muscle nicotinic acetylcholine (ACh) receptor (nAChR), a rhodamine fluorophore was tethered to a Cys side chain introduced at the ␤19 position in the M2 region of the nAChR expressed in Xenopus oocytes. This procedure led to only minor changes in receptor function. During agonist application, fluorescence increased by (⌬F͞F) Ϸ10%, and the emission peak shifted to lower wavelengths, indicating a more hydrophobic environment for the fluorophore. The dose-response relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 24 publications
6
111
0
Order By: Relevance
“…2, C and D). The blue shift in the MTSR emission peak is characteristic of an increase in hydrophobicity in the fluorophore environment, most likely reflecting a movement of the fluorophore to a more hydrophobic environment in the open state (15). As expected, MTSR-incubated oocytes expressing ␣1WT GlyRs did not show ⌬F or spectral shifts (Fig.…”
Section: Specific Mtsr Labeling Of Thementioning
confidence: 54%
See 3 more Smart Citations
“…2, C and D). The blue shift in the MTSR emission peak is characteristic of an increase in hydrophobicity in the fluorophore environment, most likely reflecting a movement of the fluorophore to a more hydrophobic environment in the open state (15). As expected, MTSR-incubated oocytes expressing ␣1WT GlyRs did not show ⌬F or spectral shifts (Fig.…”
Section: Specific Mtsr Labeling Of Thementioning
confidence: 54%
“…Finally, Dahan et al (15) investigated acetylcholine-and epibatidine-mediated ⌬F and ⌬I changes at muscle (␣␤␥␦) nAChRs via a rhodamine label attached to the ␤ subunit 19Ј position. They concluded that ⌬F reported a conformational change at the ␣␦ subunit interface.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…The conformational changes are not necessarily the same for all subunits (Dahan et al 2004;Grosman and Auerbach 2000) and structural data from electron microscopy from Torpedo californica nAChR propose that rotational movements of the a subunits promote channel gating (Miyazawa et al 2003;Unwin 2005).…”
Section: Introductionmentioning
confidence: 99%